Influence of Sleeve Gastrectomy on NASH and Type 2 Diabetes Mellitus - W. K. Karcz; D. Krawczykowski; S. Kuesters; G. Marjanovic; B. Kulemann; H. Grobe; I. Karcz-Socha; U. T. Hopt; W. Bukhari; J. M. Grueneberger (Journal of Obesity)
Background. Nonalcoholic fatty liver disease is present in up to 85% of adipose patients and may proceed to nonalcoholic steatohepatitis (NASH). With insulin resistance and obesity being the main risk factors for NASH, the effect of isolated sleeve gastrectomy (ISG) on these parameters was examined. Methods. 236 patients underwent ISG with intraoperative liver biopsy from December 2002 to September 2009. Besides demographic data, pre-operative weight/BMI, HbA1c, AST, ALT, triglycerides, HDL and LDL levels were determined. Results. A significant correlation of NASH with higher HbA1c, AST and ALT and lower levels for HDL was observed (P<.05, <.0001, <.0001, <.01, resp.). Overall BMI decreased from 45.0 ± 6.8 to 29.7 ± 6.5 and 31.6 ± 4.4 kg/m2 at 1 and 3 years. An impaired weight loss was demonstrated for patients with NASH and patients with elevated HbA1c (plateau 28.08 kg/m2 versus 29.79 kg/m2 and 32.30 kg/m2 versus 28.79 kg/m2, resp.). Regarding NASH, a significant improvement of AST, ALT, triglyceride and HDL levels was shown (P<.0001 for all). A resolution of elevated HbA1c was observed in 21 of 23 patients. Summary. NASH patients showed a significant loss of body weight and amelioration of NASH status. ISG can be successfully performed in these patients and should be recommended for this subgroup.